Different risk factors for bleeding and discontinuation between dabigatran and rivaroxaban. Issue 2 (August 2016) - Nishino, Masami; Okamoto, Naotaka; Tanaka, Akihiro; Mori, Naoki; Hara, Masahiko; Yano, Masamichi; Makino, Nobuhiko; Egami, Yasuyuki; Shutta, Ryu; Tanouchi, Jun
Abstract: Background: It is unclear whether risk factors for bleeding and discontinuation are different between dabigatran and rivaroxaban. Methods and results: We enrolled consecutive patients with atrial fibrillation who received dabigatran or rivaroxaban, had a CHADS2 score >1 and creatinine clearance >30 ml/min. During this period, only dabigatran and rivaroxaban were available as non-vitamin K oral anticoagulants (NOACs) in our hospital. We compared the clinical and demographic data and the incidence of bleeding for one year between dabigatran group and rivaroxaban group. As a result, the dabigatran group consisted of 177 patients and the rivaroxaban group consisted of 179 patients. The incidence of discontinuation was significantly higher in the dabigatran group than in the rivaroxaban group (27.7% vs. 13.4%, p < 0.001). Multivariate analysis, even after propensity score-matching analysis, revealed that there were no independent risk factors for bleeding in the dabigatran group, while in the rivaroxaban group, use of antiplatelet therapy was an independent factor correlating with bleeding. Conclusions: The risk factors for bleeding may be different between dabigatran and rivaroxaban. To avoid bleeding, rivaroxaban should be prescribed with caution or avoided in patients using antiplatelet therapy. Upon discontinuation, rivaroxaban may be more favorable than dabigatran.